ANALISIS PERAN DAN KONTRIBUSI SEKTOR PERTANIAN TERHADAP PERTUMBUHAN EKONOMI DALAM PRESPEKTIF ISLAM ( STUDI PADA KABUPATEN TULANG BAWANG ) - Munajahro, Violanida; Setyanto, Alief Rakhman (Jurnal Ilmiah Ekonomi, Manajemen dan Syariah, 2024)
The agricultural sector in an agrarian country, especially Indonesia, has an important role, where most of the population is very dependent on the primary sector, especially the agricultural sector. The existence of the agricultural sector is important for the development of a country or region because of its large contribution or role, especially in providing food needs, industrial raw material needs, contributing to foreign exchange, plays a major role in employment absorption, and can also affect increasing people's income. The aim of this study was to determine the role and contribution of the agricultural sector to economic growth in Tulang Bawang Regency. The research method used in this study was descriptive quantitative with a literature approach. The data sources used were secondary data from BPS Tulang Bawang and Lampung Province. The agricultural sector is a source of livelihood for the wider community in an agrarian country like Indonesia and is a sector that greatly contributes and plays an important role in the regional and national economy. The potential of the agricultural sector owned by the regions needs to be utilized properly by focusing on the agricultural sector through optimizing regional superior commodities. Therefore, the agricultural sector really needs to be developed as a leading sector in order to improve the regional economy.